Decision Making for Company Acquisition by ELECTRE Method - M. Gökhan Yücel; ALİ GÖRENER (International Journal of Supply Chain Management, 2016)
Growth in economy together with globalization makes global companies and investment holdings more active in international markets. This activity involves a certain level of risk as payback period of investments are very critical and correct decision on selection of companies to be invested determines success of top management of investors and also creditors. In this article an investment groups local acquisition opportunities are evaluated by ELECTRE (Elimination et choix traduisant la realite) method. In this case there are four alternatives that are accepting same price and other contractual requirements. This paper lists six important criteria that have influence on local acquisition alternatives selection in Turkey according to references: Financial performance, accreditations and authorizations, Administrative and accounting, technical infrastructure, staff expertise and experience, customer portfolio. AHP (Analytical Hierarchy Process) have been used to evaluate the criteria and then ELECTRE method is used for ranking the alternatives.